PP.62 Defying the Biological Clock: Why Are UK Women Becoming Mothers Later?. (26th April 2013) - Mills, TA; Lavender, R; Logan, J; Lavender, T
Abstract : Despite warnings regarding increased risks of infertility and poor pregnancy outcomes, more women are delaying childbearing past age 35 1 . Limited empirical research has examined the factors underlying this demographic shift. This study explored views surrounding the timing of childbearing among childless women from North-West England and portrayals of older mothers in the British Media, which is recognised as a powerful influence on health-related behaviours. In-depth qualitative analyses were conducted of: (1) The views and experiences of six women aged between 18 and 24, six women aged between 25 and 34 and six women aged 35 or more and (2) Representations of pregnancy/birth in women over 35, in 839 newspaper/magazine articles and 35 television programmes published or broadcast over a calendar month. Data were managed manually and subjected to thematic analysis. Across groups, women suggested that they were living within boundaries, defined by themselves and others ; they aspired to being a great mother or no mother; and had a desire to contribute to family and society, at multiple levels. Personal expectations and social factors contextualised decision making. Media discourses, dominated by celebrity coverage, promoted later motherhood as a means to reconcile expectations of economic and social productivity with being a 'good mother'. Medical risks were underplayed, reinforcing women's notions that later motherhood was achievable and acceptable. Effective communication of the risks associated with delayed childbearing challenges professionals and policymakers to expand the current restrictive framing of this issue. Reference: RCOG. RCOG Statement on later maternal age. London: Royal College of Obstetricians and Gynaecologists, 2009. www.rcog.org.uk/what-we-do/campaigning-and-opinions/statement/rcog-statement-later-maternal-age (accessed 27 Nov 2012).